(untitled) (Revista Iberoamericana de Bioética, 2024)
There is a limited availability of organs for pediatric donations, resulting in a large imbalance between supply and demand, forcing professionals to consider all options to improve the situation. In addition to being a part of "family-centred" endof- life care, paediatric controlled asystole donation could greatly increase overall donation by including children in paediatric palliative care, such as neonates with severe neural tube malformations and patients hospitalized at home. However, the particular clinical and human situations of these patients require special ethical considerations.